Do Harmonized Accounting Standards lead to Harmonized Accounting Practices?: An empirical study of IAS 39 in some European Union countries. - morais, ana (2007)
Since 2005, IASB standards became mandatory for publicly listed European companies in the consolidated financial statements (Rule 1606/2002 of European Union Commission). The adoption of a uniform accounting standards is expected to increase the comparability of the financial information. However, formal harmonization does not lead to a convergence in actual financial reporting practice, material harmonization, and there are some cultural, political, social and economic factors that can influence the preparation and presentation of financial statements. The objective of this paper is to investigate the level of harmonization of financial instruments reporting practice with IAS 39 (measurement of financial instruments) and to identify if different levels of harmonization are associated with firm specific factors. Based on Rahman et al. (2002) methodology, we used Jacquard Index in order to determine the level of harmonization between IAS 39 and financial reporting practice of a broad based sample of number of European listed firms in 2005. Based on these results, we also applied regression analysis to identify the firm specific characteristics that affect the level of convergence of financial instruments reporting practice. The results of this study permits to conclude that formal harmonization does not necessarily lead to material harmonization as previous studies have empirically showed.